Método para diagnóstico da eficiência bioeconômica de sistemas de produção de bovinos de corte - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The objective of this work was to develop a quantitative method to diagnose the efficiency of beef cattle production systems, differentiating the properties interviewed at respective levels of efficiency, and to point out the limiting factors to increase the efficiency of the evaluated production systems. The method developed was a quantitative questionnaire that started with the one proposed by Marques (2014), where the adaptation suggested that the quantitative questions refer to the data that serve as the basis for calculating these indicators, aiming at the correct analysis of the company. The efficiency, technology (TEC) and management (GES) drivers were used. These were divided into factors, where each factor presents the questions related to productive and economic indicators. The questionnaire was applied to 5 farms located in the West Region of Rio Grande do Sul, which have different systems of beef cattle production, which were randomly selected through the indication of professionals in the region, being: complete cycle, creates and createsrecreates. The interviews were applied together with the owners or consultants of the farms during the period from April to May 2018. The production systems presented the notes for each driver and its related factors, as well as the efficiency index (IE) of the production system. These values served to classify production systems following the criterion of a Likert scale (TROCHIM, 2002). Four different levels of efficiency were obtained in the evaluated systems: low efficiency level (NEB), medium low (NEMb), medium high (NEMa) and high (NEA). The method was adequate to present an outline of the current situation of beef cattle farms, through management and technology, since in the view of consultants who already knew the majority of the evaluated systems, the efficiency levels obtained are within than expected. The presented result shows that the method works, highlighting highlights and those that are limited within the business, adequately analyzing performance indicators of production systems. However, adjustments must be studied in order for the method to present results even closer to the productive reality of the different productive systems of existing beef cattle.
Keywords: Gestão; Indicadores de eficiência; Pecuária de corte; Beef cattle; Efficiency indicators; Management; CNPQ::CIENCIAS AGRARIAS